2016
DOI: 10.1155/2016/9057593
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in the Aging Muscles of Flies and Mice: New Perspectives for Old Characters

Abstract: Sarcopenia is the loss of muscle mass accompanied by a decrease in muscle strength and resistance and is the main cause of disability among the elderly. Muscle loss begins long before there is any clear physical impact in the senior adult. Despite all this, the molecular mechanisms underlying muscle aging are far from being understood. Recent studies have identified that not only mitochondrial metabolic dysfunction but also mitochondrial dynamics and mitochondrial calcium uptake could be involved in the degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 107 publications
1
15
0
Order By: Relevance
“…The other widely used phenotypic marker of aging is the age-related decline of motility. Decreased motility with aging is associated with muscle atrophy and dysfunction [40]. Recent studies have shown that genetic intervention with antioxidant genes, such as cat and sod-1 , or nutritional intervention with antioxidants, such as silymarin and selenocysteine, can modulate age-related muscle dysfunction [16, 41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…The other widely used phenotypic marker of aging is the age-related decline of motility. Decreased motility with aging is associated with muscle atrophy and dysfunction [40]. Recent studies have shown that genetic intervention with antioxidant genes, such as cat and sod-1 , or nutritional intervention with antioxidants, such as silymarin and selenocysteine, can modulate age-related muscle dysfunction [16, 41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…There are many reasons for the increase in ROS; the decreased cellular antioxidant capacity caused by decreased antioxidant enzyme (superoxide dismutase, catalase and glutathione peroxidase) activity [15] is an important factor leading to increased ROS production. Studies have shown that the activity of antioxidant enzymes is gradually reduced during the process of skeletal muscle aging [15]. The overexpression of skeletal muscle catalase in aged mice can improve age-related mitochondrial oxidative stress and dysfunction, and enhance mitochondrial energy metabolism [4].…”
Section: Oxidative Stress Levels Increase In Aging Skeletal Musclementioning
confidence: 99%
“…Disturbances in calcium regulation and mitochondrial homeostasis may also contribute to the decline of muscle performance in aging (for review, see Del Campo, Jaimovich, & Tevy, 2016). Indeed, Pietrangelo et al.…”
Section: Regulating Factors Of Mptp and Agingmentioning
confidence: 99%